2021
DOI: 10.2147/jmdh.s330041
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Burdens During the COVID-19 Pandemic: A Qualitative Systematic Review

Abstract: Background:The global healthcare system is continuing to confront major challenges during the current COVID-19 pandemic, with the second wave the deadliest one to date. This study aimed to identify and explore the challenges and burdens of frontline healthcare workers during the current pandemic, and to help prepare workforce support plans for them now and in the future. Methods: A qualitative systematic review method involving thematic synthesis without meta-analysis was used to analyze relevant studies from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 36 publications
9
113
1
3
Order By: Relevance
“…In addition, our findings are broadly consistent with a recent systematic review [33], where, for example, burnout was identified as an overarching, cross-cutting theme. The current study is nevertheless unique in exploring a highly adaptive system that was demonstrated to have reacted very successfully during the crisis itself; it also adds a theoretical formulation and mapping of findings for future development and testing to help guide planning and policy.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…In addition, our findings are broadly consistent with a recent systematic review [33], where, for example, burnout was identified as an overarching, cross-cutting theme. The current study is nevertheless unique in exploring a highly adaptive system that was demonstrated to have reacted very successfully during the crisis itself; it also adds a theoretical formulation and mapping of findings for future development and testing to help guide planning and policy.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…A recently published systematic review mentioned that inadequate preparedness for and the unknown information about COVID-19 was the main reason for the accumulation of negative emotions. 6 At the early stages of the COVID-19 pandemic, a study 15 found that about one-third (342/994) of the healthcare providers in Wuhan, China had significant mental health disturbances. Among them, 6.2% (62 of 994) had severe disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pandemic increases post-traumatic stress disorder, leading to burnout and interruption of medical work. 6 A meta-analysis with 21 studies shows an urgent need for interventions to prevent or reduce the mental health problems of intensive care unit (ICU) medical staff caused by COVID-19. 7 The results of two systematic reviews also indicate that nurses working on the frontline during the COVID-19 pandemic have experienced psychological, social and emotional distress in coping with work demands, social relationships and their personal lives.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous qualitative studies about HCWs’ psychology under COVID-19 pandemic conditions. ( Billings et al., 2021 ; Koontalay et al., 2021 ) But as mentioned in introduction, there is no study about cohort isolated HCWs who work in the psychiatric hospital. We found a qualitative study about HCWs’ experiences in cohort isolation units because of carbapenemase-producing Enterobacterales infection prevention.…”
Section: Discussionmentioning
confidence: 99%